(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present paper deals with the mathematical model on vibrational analysis of damped non-homogeneous annular plate considering parameters of changing thickness and Winkler’s type elastic foundation. Here thickness and non-homogeneity are considered to vary exponentially. Numerical simulation is performed through QSIT (Quintic spline interpolation technique) which provides approximate results as per desired accuracy for two different combination of edge conditions CC & CS and we obtained first three modes of frequency parameter. Accuracy for the solution to our assumed mathematical model is affirmed by comparing obtained results with those available in previous literature. MATLAB (2015) is used to produced and present the results of above mathematical model.